MANAGING WATER DEMAND AND SUPPLY UNDER SILTATION CHALLENGES: INTEGRATED STRATEGIES FOR THE HAMMAM DEBAGH RESERVOIR IN GUELMA PROVINCE, EASTERN ALGERIA - Berredjem A.F.; Boumaiza A. (International Journal of Innovative Technologies in Social Science, 2024)
This study analyses water demand management scenarios in Guelma Province, which heavily relies on the Hammam Debagh Dam, to evaluate challenges and opportunities in water security. Sedimentation in the dam significantly reduces water storage capacity, exacerbating the water crisis. The research employs a combination of hydrological modeling, scenario analysis, and stakeholder consultations. Hydrological data were used to simulate the impacts of sedimentation on water storage capacity. Various management scenarios, such as river diversion and reforestation, were modeled to assess their effectiveness in reducing unmet water demand. Stakeholder consultations provided insights into local perceptions and implementation challenges. The results project an unmet water demand of 82 million cubic meters by 2060 in the baseline scenario. Implementing river diversion could reduce unmet demand by 16%, while reforestation offers a 7% reduction. Combining these measures could achieve a 21% reduction in unmet water demand. This underscores the critical importance of integrated approaches for holistic water resources management and the urgent need for effective action. The study highlights the necessity of an integrated approach to mitigate unmet water demand, which is essential for sustainable water management. It also advocates for proactive collaboration among stakeholders to address environmental, economic, and social challenges, ensuring the long-term resilience of water resources in the region.